Protein modification by thiolactone homocysteine chemistry: a multifunctionalized human serum albumin theranostic - Popova, Tatyana V; Krumkacheva, Olesya A; Burmakova, Anna S; Spitsyna, Anna S; Zakharova, Olga D; Lisitskiy, Vladimir A; Kirilyuk, Igor A; Silnikov, Vladimir N; Bowman, Michael K; Bagryanskaya, Elena G; Godovikova, Tatyana S (MedChemComm, 2020)
As the most abundant protein with a variety of physiological functions, albumin has been used extensively for the delivery of therapeutic molecules. Thiolactone chemistry provides a powerful tool to prepare spin-labeled albumin-based multimodal imaging probes and therapeutic agents. We report the synthesis of a tamoxifen homocysteine thiolactone derivative and its use in thiol-'click' chemistry to prepare multi-functionalized serum albumin. The released sulfhydryl group of the homocysteine functional handle was labeled with a nitroxide reagent to prepare a spin-labeled albumin-tamoxifen conjugate confirmed by MALDI-TOF-MS, EPR spectroscopy, UV-vis and fluorescent emission spectra. This is the basis for a novel multimodal tamoxifen-albumin theranostic with a significant (dose-dependent) inhibitory effect on the proliferation of malignant cells. The response of human glioblastoma multiforme T98G cells and breast cancer MCF-7 cells to tamoxifen and its albumin conjugates was different in tumor cells with different expression level of ERα in our experiments. These results provide further impetus to develop a serum protein for delivery of tamoxifen to cancer cells. A tamoxifen-homocysteine conjugate provides a tool to prepare a multifunctionalized albumin theranostic with a significant cytotoxicity on the malignant cells.